Predictive Pharmacological Activity of Galangal Rhizome (Alpinia galanga (L.) Willd.) Through in Silico Analysis as an Effort to Accelerate The Research of Indonesian Medicinal Plants - Jamil, Ahmad Shobrun; Ahmad, Mujahidin (El-Hayah : Jurnal Biologi, 2020)
Indonesia has high biodiversity, especially plant species. There are many benefits that can be Obtained from various plants that grow in Indonesia, one of which is as a health supplement or medicinal raw material. Fast researches are important in the use of these plants so that bio-based products can be widely accepted. One of the important fast methods in analysing the benefits of plant chemical compounds is the in-silico prediction utilizing metadata spread over various pages providing scientific data about plants, their chemical compound content and biological activity. This study was focused on predictively observing the biological activity of the compounds in the rhizome of Alpinia galanga. The research method is by analysing metadata from various sources. Data on the content of chemical compounds can be accessed through the pageÂ https://phytochem.nal.usda.gov/, classification of metabolite compounds contained in plants using http://classyfire.wishartlab.com/, prediction of absorption, distribution, metabolism and excretion (ADME) uses http://www.swissadme.ch/, to determine the relationship between plant compounds and body proteins, http://www.swisstargetprediction.ch/ and prediction of cellular mechanisms seen through https://string-db.org. Based on in silico analysis by utilizing some of the above software, it can be seen that the rhizome of the Alpinia galangal plant has 80 active compounds, 47 have high bioavailability and 9 compounds with tight cell proteins. Based on in silico exploration, it is also known that A. galangal has potential as an antioxidant, antimicrobial, anti-cancer and various other pharmacological activities